mHealth Apps for Self-Management of Chronic Conditions in France: What Is out There? - Prado, Luiza; Carpentier, Camille; Préau, Marie; Schott, Anne-Marie; Dima, Alexandra (PloS one, 2019)
mHealth apps use is rapidly increasing and has high potential value for people with chronic conditions, supporting behaviour change for self-management and improving patient-provider communication. To build a well-functioning app development environment, we need to examine the range of available apps according to their variability and content. A review of Google Play apps revealed limited availability for chronic self-management in France among substantial unrelated content. Most apps' content was difficult to understand and act upon.